Ionic Conductivity Studies of Biodegradable Polymer Electrolyte for Mg Ion Batteries - Garidepalli, Tejaswi; Parthiban, V.; Sunita Sundari, G.; Erothu, Harikrishna (Asian Journal of Chemistry, 2022)
Solid biopolymer electrolyte was prepared from potato starch (PS) blended with polyvinyl pyrrolidone (PVP) polymer and magnesium sulphate (MgSO4) using solution casting technique. XRD revealed the amorphous structure and FTIR studies shows complexation of the salt with polymer with different weight ratios for PS:PVP:MgSO4. Ionic conductivity was calculated using AC impedance studies and the sample with the concentration of PS:PVP:MgSO4 (35:35:30 wt.%) is having the highest ionic conductivity 4.2142 × 10-4 S/cm at 273 K. For this sample, electrochemical studies like linear sweep voltammetry have given the stable voltage and the stable redox potential obtained from cyclic voltammetric studies. Dielectric studies have proven the charge holding capacity thus shows stability in conducting the ions. Thus, these results strengthen the solid biopolymer electrolyte to use as electrolyte in the Mg2+ ion-based batteries.